The role of the WatchPAT device in the diagnosis and management of obstructive sleep apnea - Campbell, Christina D.; Sulaiman, Imran (Frontiers in Sleep, 2023)
Obstructive Sleep Apnea (OSA) is a common condition, affecting an estimated 936 million individuals worldwide, leading to considerable demand for diagnostic services. The current gold standard for diagnosis - polysomnography is resource intensive and inconvenient for patients and healthcare providers. The WatchPAT is an unobtrusive device for home OSA diagnosis. It utilises peripheral arterial tomography in conjunction with heart rate, oximetry, actinography and respiratory movements for the diagnosis of OSA. It has good correlation with polysomnography for OSA diagnosis, and also reports sleep time and sleep staging. The WatchPAT device has reported sensitivities of 81-95%, specificities of 66-100%, positive predictive value of 79-96% and negative predictive value of 92% for determination of AHI. Its use has also been studied and validated in a variety of patient populations, including children, the elderly, during pregnancy and those with comorbid medical conditions. The device has also been adapted for use in screening for cardiac arrythmias and central sleep apnoea, although both uses have not been adapted widely. With the emergence of telemedicine and increasing demand for sleep services, the WatchPAT device can be a useful tool to aid in OSA diagnostics.